Capillary electrophoretic methods for quality control analyses of pharmaceuticals: A review. Issue 1 (28th September 2020) - Řemínek, Roman; Foret, František
Abstract: Capillary electrophoresis represents a promising technique in the field of pharmaceutical analysis. The presented review provides a summary of capillary electrophoretic methods suitable for routine quality control analyses of small molecule drugs published since 2015. In total, more than 80 discussed methods are sorted into three main sections according to the applied electroseparation modes (capillary zone electrophoresis, electrokinetic chromatography, and micellar, microemulsion, and liposome‐electrokinetic chromatography) and further subsections according to the applied detection techniques (UV, capacitively coupled contactless conductivity detection, and mass spectrometry). Key parameters of the procedures are summarized in four concise tables. The presented applications cover analyses of active pharmaceutical ingredients and their related substances such as degradation products or enantiomeric impurities. The contribution of reported results to the current knowledge of separation science and general aspects of the practical applications of capillary electrophoretic methods are also discussed.